KEBERMAKNAAN HIDUP MANTAN PUNKERS - Argo, Abi Risa Bayu; Karyono, Karyono; Kristiana, Ika Febrian (Faculty of Psychology, Diponegoro University, 2014)
AbstractThe meaning in life is considered as an essential, truthful, and valuable thing for a person that deserved to be the goals in life. This study aims to describe and understand the meaning in life of ex punkers. A qualitative phenomenological approach was used in this study. Data were collected using depth interview and observation.Two subjects participated in the study and were approached using a typical purposive sampling. Findings showed that the meaning in life of these ex punkers were determined by the life before they joined punk, the life within punk communities, and the life after they left punk communities. From all the process they had gone through, there were similarities within the two subjects. They believed that life should be beneficial to others, one should be willing to share with others and to be respectful to others, and to honor solidarity and caring to others. The meaning in life of both subjects was derived from creative values as well as experiential values.